Metabolism of cyclic phenones in rainbow trout in vitro assays. (1st February 2020) - Serrano, Jose; Tapper, Mark A.; Kolanczyk, Richard C.; Sheedy, Barbara R.; Lahren, Tylor; Hammermeister, Dean E.; Denny, Jeffrey S.; Hornung, Michael W.; Kubátová, Alena; Kosian, Patricia A.; Voelker, Jessica; Schmieder, Patricia K.
Abstract: 1. Cyclic phenones are chemicals of interest to the USEPA due to their potential for endocrine disruption to aquatic and terrestrial species. 2. Prior to this report, there was very limited information addressing metabolism of cyclic phenones by fish species and the potential for estrogen receptor (ER) binding and vitellogenin (Vtg) gene activation by their metabolites. 3. The main objectives of the current research were to characterize rainbow trout (rt) liver slice-mediated in vitro metabolism of model parent cyclic phenones exhibiting disparity between ER binding and ER-mediated Vtg gene induction, and to assess the metabolic competency of fish liver in vitro tests to help determine the chemical form (parent and/or metabolite) associated with the observed biological response. 4. GC-MS, HPLC and LC-MS/MS technologies were applied to investigate the in vitro biotransformation of cyclobutyl phenyl ketone (CBP), benzophenone (DPK), cyclohexyl phenyl ketone (CPK) mostly in the absence of standards for metabolite characterization. 5. It was concluded that estrogenic effects of the studied cyclic phenones are mediated by the parent chemical structure for DPK, but by active metabolites for CPK. A definitive interpretation was not possible for CBP and CBPOH (alcohol), although a contribution of both structures to gene induction is suspected.